Concurrent Gaussian Elimination - Ulrich Berger (Mathematics for Computation (M4C), 2023)
Working in a semi-constructive logical system that supports the extraction of concurrent programs, we extract a program inverting non-singular real valued matrices from a constructive proof based on Gaussian elimination. Concurrency is used for efficient pivoting, that is, for finding an entry that is apart from zero in a non-null vector of real numbers.